Effect of nanocapsulated of rye (Secale cereale L.) extracts on germination components of dodder (Cuscuta campestris Y.(dodder)) and purslane (Portulaca oleracea L.) - Mehrnoosh Jadidi; مرجان دیانت; Asa Ebrahimi (علوم و فناوری بذر ایران, 2021)
Replacing biological herbicides instead of chemical herbicides has not only had adverse environmental effects but also has the advantage of biodegradability. In this study, the effect of rye extract in biocompatible polymer chitosan / alginate nanocapsule with non nonocapsulated extract on dodder and purslane were investigated. The experiment was conducted in a completely randomized design with factorial arrangement. Extracts of shoot and root were evaluated at different concentrations (0, 6.25, 12.5, 25, 50 and 100%) on germination percentage, germination rate, radicle and plumule length, radicle and plumule fresh weight. The results showed that the particles were relatively spherical with a smooth surface and the shoot and root extracts had particle sizes of 113 and 350 nm and 71.4 to 129 nm, respectively. Nano-extract of shoot and root reduced germination of sauces seed to zero at concentrations of 25, 50 and 100%. The highest germination percentage of purslane seed belonged to control treatment (78.26%) which was significantly different from other treatments. Shoot and root nano extracts caused complete inhibition of purslane seed germination at concentrations of 25, 50 and 100%, which were significantly different from other treatments. Increasing concentration of rye extract increased the inhibition percentage of studied traits and nanocapsulation increased allelopathic effect of rye extract.